A variant of the Nijmegen breakage syndrome with unusual cytogenetic features and intermediate cellular radiosensitivity. Issue 3 (March 1997) - Tupler, R; Marseglia, G L; Stefanini, M; Prosperi, E; Chessa, L; Nardo, T; Marchi, A; Maraschio, P
Abstract : We report the first Italian case of Nijmegen breakage syndrome (NBS). The proband is an immunodeficient, microcephalic, 11 year old boy with a "bird-like" face. He developed a T cell rich B cell lymphoma. Spontaneous chromosomal instability was detected in T and B lymphocytes and fibroblasts; chromosomes 7 and 14 were only sporadically involved in the rearrangements and no clonal abnormality was present. The patient appeared to be sensitive both to ionising radiation and to bleomycin, although his sensitivity did not reach the level of AT reference cells. After bleomycin treatment, inhibition of DNA synthesis was low when compared with normal cells, but higher than observed in an AT reference strain. Moreover, cell cycle analysis, after drug exposure, showed a progressive reduction in the percentage of S phase cells, but the G1 arrest, found in normal cells, was not observed. On clinical evaluation our patient shares features with NBS subjects, but cytogenetic and cell biological data do not completely overlap with those reported in Nijmegen breakage syndrome. The ethnic origin of our patient might account for these differences, as expression of different allelic forms at the NBS locus.